(untitled) (Educological discourse, 2015)
The features of concept «information» are reflected as a pedagogical category of process of forming of informative competence. An attempt to ground theoretical principles of process of forming of informative competence on the basis of study of features of concept «information». Investigate the scientifically-category vehicle of informational and alternative pedagogics as to the division of applied informolohiya is done.